Carbonylation is a hallmark of oxidative stress induced by lipid peroxidation products, 4-hydroxy-2-nonenal and 4-hydroxy-2- hexenal, on insulin signalling in L6 myoblasts. - Chionh, Yok Hian. (2009)
Peripheral insulin resistance is one of the defining characteristics of type 2 diabetes - a metabolic disorder commonly associated with oxidative stress. Obesity and exposure to atmospheric oxidants, such as ozone gas, induces oxidative stress which increases lipid peroxidation. However, it is still unclear how major lipid peroxidation end products, 4-hydroxy-2-nonenal (HNE) and 4-hydroxy-2-hexenal (HHE) disrupt insulin signaling in muscles. Furthermore, the lack of appropriate models and common measurements has hampered inferences from being drawn from in vivo and in vitro experiments. Exposure of Wistar rats to ozone and incubation of rat L6 myoblasts with non-toxic concentrations of HHE or HNE revealed that in both cases cellular carbonylation levels were significantly increased. In addition, HNE and HHE-Micheal adducts were detected in immunoblots of L6 cell lysate. Though both HHE and HNE were able to impair glucose uptake in response to insulin in L6 cells and antioxidative pre-treatment of L6 cells with N-acetyl-cysteine (NAC) or 3H-1,2-dithiole-3-thione (D3T) successfully prevented oxidative damage in the form of HHE or HNE adduct formation in L6 cells, we have curiously found that HHE unlike HNE was neither able to decrease insulin receptor substrate (IRS)-1 tyrosine phoshorylation nor prevent the recruitment of phosphoinositide 3-kinases (PI3k). Put together, our results suggests that carbonylation is common in various forms of oxidative stresses and that HHE and HNE affect different members of the insulin signaling cascade.